Obesity as a Limiting Factor for Remote Ischemic Postconditioning-Mediated Neuroprotection after Stroke - Klaudia Kotorová; Jana Končeková; Miroslav Gottlieb; Martin Bona; Petra Bonová (Journal of Obesity & Metabolic Syndrome, 2024)
Background : Remote ischemic postconditioning (RIPostC) may protect the brain from ischemia/reperfusion (I/R) injury. The association between RIPostC and obesity has not yet been extensively studied. Methods : Twelve-week-old male Zucker diabetic fatty (ZDF; n=68) and Zucker diabetic lean (ZDL; n=51) rats were subjected to focal cerebral ischemia for 90 minutes, followed by 24 hours of reperfusion. RIPostC was performed with 5-minute I/R cycles using a tourniquet on the right hind limb. Results : The results showed a negative association between obesity and neurological impairment in ischemic animals. We observed a 70% greater infarct size in ZDF rats compared with their lean counterparts, as evaluated by 2,3,5-triphenyltetrazolium chloride staining. To measure the total fragmented DNA in peripheral lymphocytes, comet assay was performed. Obese rats exhibited higher levels of DNA damage (by approximately 135%) in peripheral blood lymphocytes even before the induction of stroke. RIPostC did not attenuate oxidative stress in the blood in obese rats subjected to ischemia. Focal cerebral ischemia increased core and penumbra tissue glutamate release in the brain and decreased it in the blood of ischemic ZDL rats, and these changes improved following RIPostC treatment. However, changes in blood and tissue glutamate content were not detected in ischemic ZDF rats or after RIPostC intervention. Conclusion : Our findings suggest that obese animals respond more severely to ischemia-reperfusion brain injury. However, obese animals did not achieve neuroprotective benefits of RIPostC treatment.